Personal Touch di Era Digital: Refleksi Komunikasi Langsung dalam Program Migrasi Perbankan (Studi Kasus Magang di BSI KCP Surabaya Rungkut 1) - Samsiah, Toyyibatus; Arifin, Sirajul (CV. ITTC INDONESIA, 2025)
Mobile banking application migration programs often face challenges in the form of customer resistance and anxiety towards new technology. This qualitative case study aims to analyze the process, effectiveness, and dynamics of personal communication (via WhatsApp/telephone) implemented in the application migration program at Bank Syariah Indonesia (BSI) KCP Surabaya Rungkut 1, from the reflective perspective of interns as direct participants. Data was collected through participatory observation and reflective documentation during the three-week program period, then analyzed thematically. The findings show three patterns of customer responses (Skeptical-Aggressive, Cooperative-Interactive, Verificative-Analytical) that require different handling strategies. A critical point occurred when interactions evolved from technical migration transactions to discussions about other products, marking the formation of trust and relational value. The main obstacles were customer technical barriers and network limitations. Critical reflection using four theoretical lenses reveals that personal communication functions multidimensionally: as a catalyst for technology acceptance (Technology Acceptance Model), a manifestation of service quality (SERVQUAL/IBSQ), a means of building interpersonal trust, and an investment in relationship marketing. The practical implication is that a personal approach to digital transformation should be viewed as a strategic investment that not only pursues adoption targets but, more importantly, converts the momentum of change into strengthening long-term customer loyalty.